Estudos dos comportamentos eletroquímicos de polianilina e de polianilinas substituídas utilizando técnicas simultâneas e in situ de efeito miragem, microbalança de quartzo e voltametria cíclica - Pollyanna Mara da Silva (2015)
Study, electrosynthesis and characterization of intrinsically conductive polymers (ICP's) with potential application in organic optoelectronics are presented in this work. Thin films of polyaniline (PANI) and derivative polyanilines were produced, such as poly(otoluidine) (POT), poly(o-methoxyaniline) (POMA) and poly(2,5-dimethoxyaniline) (PDMA). The influence of the cation size during the electropolymerization of all commercial monomers and the electrochemical behavior of each corresponding polymer was studied by Cyclic Voltammetry (CV) in the electrolyte: lithium and cesium perchlorate. This study allowed us to evaluate the influence that the cation promotes the electrochemical properties these ICP’s. The loss of charge of each polymer also was performed using CV. Simultaneous Measures and in situ of Mirage Effect (ME), Quartz Crystal Microbalance (QCM) and Cyclic Voltammetry (CV) were used for the electrosynthesis and electrochemical characterization of PDMA. The PDMA electropolymerization kinetics in the presence of electrolytes of lithium perchlorate (LiClO4), sodium (NaClO4), potassium (KClO4), rubidium (RbClO4) and cesium (CsClO4) was characterized coupling QCM and VC. The PDMA electropolymerization and electrochemical behavior in solution containing LiClO4 salts and CsClO4 showed the influence of the cation mass transport and its electrochemical properties. To confirm the achievement of the polyaniline doped state (emeraldine salt) spectroscopy analysis in the region of Infrared Attenuated Total Reflection (IV-ATR) has been employed. Poly(o-toluidine) films were characterized according to charge transfer transportation on their matrix by dc electrical conductivity. The temperature influence in the range (323 - 493) k and the kind of dopant in conductive properties of this polymer were studied. To this end, we used to LiClO4, NaClO4 and KClO4 as dopants during the electropolymerization. Scanning Electron Microscopy images (SEM) were obtained in order to characterize the influence of doping in the morphology of POT films. It was observed that the kind of dopant influences the electrical conductivity in the amount of activation energy, Eg, and morphology of these materials. Poly(o-toluidine) films doped with KClO4 and NaClO4 demonstrated thermal activated behavior in the temperature range (323 - 413) k characteristic of semiconductor materials. However, POT synthetized in the presence of LiClO4 showed metallic behavior in the whole temperature range.